2015
DOI: 10.1007/s11356-015-5394-6
|View full text |Cite
|
Sign up to set email alerts
|

Modelling benzo[a]pyrene in air and vegetation for different land uses and assessment of increased health risk in the Iberian Peninsula

Abstract: The ability of the modelling system WRF+CHIMERE implemented with high spatial and temporal resolution over the Iberian Peninsula (IP) to represent the levels of benzo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Two modelling studies assessed the amount of air pollutants removed/intercepted by trees and compared them to established air quality and health standards [47,48]. In the cross-sectional studies, several positive outcomes and a few neutral findings were reported.…”
Section: Air Pollutants and Respiratory Conditionmentioning
confidence: 99%
“…Two modelling studies assessed the amount of air pollutants removed/intercepted by trees and compared them to established air quality and health standards [47,48]. In the cross-sectional studies, several positive outcomes and a few neutral findings were reported.…”
Section: Air Pollutants and Respiratory Conditionmentioning
confidence: 99%
“…They are ubiquitous in the environment in gas and particulate form and can have an effect on human health through several forms of exposure (inhalation, diet, etc.). Among them, benzo(a)pyrene (BaP), with a five-aromatic ring molecular structure (thus present in the atmosphere mainly as particulate matter) (Ratola and Jiménez-Guerrero 2015) is possibly the most studied congener of this group of compounds and is often considered as the PAHs "representative" in environmental research (Nisbet and LaGoy 1992;Ratola and Jiménez-Guerrero 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They are ubiquitous in the environment in gas and particulate form and can have an effect on human health through several forms of exposure (inhalation, diet, etc.). Among them, benzo(a)pyrene (BaP), with a five-aromatic ring molecular structure (thus present in the atmosphere mainly as particulate matter) (Ratola and Jiménez-Guerrero 2015) is possibly the most studied congener of this group of compounds and is often considered as the PAHs "representative" in environmental research (Nisbet and LaGoy 1992;Ratola and Jiménez-Guerrero 2017).…”
Section: Introductionmentioning
confidence: 99%